Hasil Dan Nisbah Kesetaraan Lahan Dua Varietas Cabai Merah (Capsicum annum L.) Yang Ditumpangsarikan Dengan Kacang Tanah Di Lahan Kering - Safta, Laila; Jaya, I Komang Damar; Santoso, Bambang Budi; Jayaputra, Jayaputra (LPPM Universitas Mataram, 2024)
Drylands with limited resource support need to increase their productivity. One indicator of land productivity is the land equivalence ratio (LER). This research aimed to study the growth and yield of red chili due to the effect of varieties and peanut planting times in intercropping systems to increase dryland productivity. One experiment was conducted in Amor-amor Hamlet, Gumantar Village, Kayangan Sub-district, North Lombok Regency, from March to August 2023. The red chili varieties tested were Baja MC (hybrid) and Landung (non-hybrid). Meanwhile, peanut (Hypoma 2 variety) planting time was at the same time, one week after planting (WAP) of chili and 3 WAP. The treatments were arranged factorially using a Randomized Block Design with three replications. All component crops had monoculture treatments to calculate LER. The results showed no interaction between variety and planting time on all parameters observed. Variety had no significant effect on growth and LER but significantly affected the yield of chili. The Landung variety produced higher yields than the Baja MC variety. Planting time treatment had no significant effect on growth and LER but significantly affected the yield of chili. The planting time of peanut that produced the highest yield was 3 WAP. The intercropping of chili with peanuts at all planting times increased dryland productivity with LER values greater than 1.0